ASUHAN KEPERAWATAN PADA PASIEN CHRONIK KIDNEY DISEASE (CKD) DENGAN PEMBERIAN INTERVENSI TERAPI PIJAT KAKI TERHADAP PENURUNAN TEKANAN DARAH - Shella Damayanti; Meynur Rohmah; Uang Musaeri; Zahrah Maulidia Septimar (Nusantara Hasana Journal, 2022)
Chronic kidney disease is a progressive and slow progression of kidney failure in each nephron (usually lasts several years and is reversible). Kidney disease often occurs in association with critical illness, progresses rapidly in a matter of days to weeks and is usually reversible if the patient can survive the critical illness (E. K. Sari, 2020). which is a state of abnormally increased blood pressure that lasts for some time is known by performing blood pressure exchanges. According to the WHO (Word Health Organization) limit blood pressure to normal if the blood pressure is below < 130/85 mmHg while if it is more than 140/90 mmHg it is stated as hypertension. Interventions to lower blood pressure in 2 ways using pharmacology and non-pharmacology. Interventions using pharmacology are by consuming drugs and medical actions. Meanwhile, non-pharmacological interventions are taking herbs and traditional therapies such as reflexology (foot massage). Reflexology is the oldest treatment in the world, reflexology was first discovered in Mesi in 2500BC. Objective: To find out how effective foot massage relaxation therapy can reduce blood pressure in patients with chronic kidney disease (CKD). The author implements nursing care for CKD (Chronic Kidney Disease) patients by applying foot massage therapy relaxation techniques. The results of the study of reducing blood pressure after foot massage therapy. Based on the results of interventions and implementations that have been proven to be effective for lowering blood pressure without long-term side effects